2017
DOI: 10.3847/1538-4357/aa74af
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Water and Ammonia in Nearby Galaxies (SWAN): Resolved Ammonia Thermometry, and Water and Methanol Masers in the Nuclear Starburst of NGC 253

Abstract: We present Karl G Jansky Very Large Array molecular line observations of the nearby starburst galaxy NGC 253, from SWAN: "Survey of Water and Ammonia in Nearby galaxies". SWAN is a molecular line survey at centimeter wavelengths designed to reveal the physical conditions of star forming gas over a range of star forming galaxies. NGC 253 has been observed in four 1GHz bands from 21 to 36 GHz at 6 ∼ 100 pc) spatial and 3.5 km s −1 spectral resolution. In total we detect 19 transitions from seven molecular and at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(101 citation statements)
references
References 69 publications
6
93
2
Order By: Relevance
“…The only extragalactic source for which there has been a detailed investigation of the relationship between classI methanol maser emission and other molecular lines is NGC 253 (Ellingsen et al 2017b;Gorski et al 2017). Hence, the reason why we observe 36.2 GHz class I methanol maser emission offset to the southeast of the center of NGC 4945 and not at other locations is largely speculation.…”
Section: Properties Of Methanol Maser Environmentmentioning
confidence: 73%
“…The only extragalactic source for which there has been a detailed investigation of the relationship between classI methanol maser emission and other molecular lines is NGC 253 (Ellingsen et al 2017b;Gorski et al 2017). Hence, the reason why we observe 36.2 GHz class I methanol maser emission offset to the southeast of the center of NGC 4945 and not at other locations is largely speculation.…”
Section: Properties Of Methanol Maser Environmentmentioning
confidence: 73%
“…As the relative abundance of ortho versus para ammonia is not known, temperatures can only be estimated from two para states or two ortho states. For T 12 , the -T T rot kin conversion (Table 4 and Figure 5 in Ott et al 2011; see also Morris et al 1973) flattens, which prevents a reliable derivation of temperatures above ∼50-60 K. T 24 , T 45 , and T 36 do not suffer such problems (Gorski et al 2017) and yield very similar results. The corresponding maps for T 12 , T 45 , and T 36 can be found in Appendix E.…”
Section: Results Of the Hyperfine Structure Fittingmentioning
confidence: 97%
“…Detections of ammonia span a large range of sources from circumstellar envelopes (e.g., Betz et al 1979) to galactic dark clouds (e.g., Ho et al 1978) and nearby galaxies such as NGC 253 (e.g., Ott et al 2005;Lebrón et al 2011;Mangum et al 2013;Gorski et al 2017) to heavily star-forming galaxies like ultraluminous infrared galaxies (ULIRGS; e.g., Arp 220, Ott et al 2011;Zschaechner et al 2016) and even at high redshift (z=0.9) as absorption against continuum emission (Henkel et al 2008). In the GC, SWAG offers high-resolution (∼0.9 pc) interferometric ammonia maps that show the intermediate-density gas structure most relevant to the stream model because large-scale diffuse emission 1 4 (3.3 pc at 8.3 kpc) 20 is filtered out by the ATCA interferometer in this setup.…”
Section: Introductionmentioning
confidence: 99%
“…Meier & Turner 2005;Meier & Turner 2012;Martín et al 2015;Saito et al 2017;Ueda et al 2017;Tosaki et al 2017), and the distribution of warm molecular gases in NGC 253 is also investigated (e.g. Ott et al 2005;Krips et al 2016;Gorski et al 2017). Nevertheless, the spatial resolution of these observations are limited to ∼ 30-100 pc, and the drastic chemical diversity among even smaller 10-pc scale clumps has not been unveiled until this work.…”
Section: Line Profiles and Emission Parametersmentioning
confidence: 99%
“…Mauersberger et al (2003) have conducted single dish observations with the spatial resolution of 40 (corresponding to 680 pc), and have shown that two velocity components have the rotation temperatures of 142 K and 100 K, respectively. Interferometric observations with the resolution of 6 (corresponding to 100 pc) have suggested that the molecular gas within the central kpc of NGC 253 could be best described by a two kinetic temperature model with 130 K and 57 K component (Gorski et al 2017). In addition to supporting these previous studies, we also reveal that hot molecular gases (∼ 100 K) are localized in a 10-pc scale star-forming clump, and this is strongly suggesting that high molecular temperature plays a major role in bringing the chemically rich environment.…”
Section: The Localization Of Hot Molecular Gases and Chemically Rich mentioning
confidence: 99%